Targeting Rho-associated coiled-coil forming protein kinase (ROCK) in cardiovascular fibrosis and stiffening. (2nd January 2020) - Yu, Brian; Sladojevic, Nikola; Blair, John E.; Liao, James K.
ABSTRACT: Introduction : Pathological cardiac fibrosis, through excessive extracellular matrix protein deposition from fibroblasts and pro-fibrotic immune responses and vascular stiffening is associated with most forms of cardiovascular disease. Pathological cardiac fibrosis and stiffening can lead to heart failure and arrythmias and vascular stiffening may lead to hypertension. ROCK, a serine/threonine kinase downstream of the Rho-family of GTPases, may regulate many pro-fibrotic and pro-stiffening signaling pathways in numerous cell types. Areas covered : This article outlines the molecular mechanisms by which ROCK in fibroblasts, T helper cells, endothelial cells, vascular smooth muscle cells, and macrophages mediate fibrosis and stiffening. We speculate on how ROCK could be targeted to inhibit cardiovascular fibrosis and stiffening. Expert opinion : Critical gaps in knowledge must be addressed if ROCK inhibitors are to be used in the clinic. Numerous studies indicate that each ROCK isoform may play differential roles in regulating fibrosis and may have opposing roles in specific tissues. Future work needs to highlight the isoform- and tissue-specific contributions of ROCK in fibrosis, and how isoform-specific ROCK inhibitors in murine models and in clinical trials affect the pathophysiology of cardiac fibrosis and stiffening. This could progress knowledge regarding new treatments for heart failure, arrythmias and hypertension and the repair processes after myocardial infarction.